Bioethical reflections about the woman and the feminine from the personalism of Karol Wojtyla - Padilla Segura, Nancy Beatriz (2020)
In this article, we refer to the main foundations that the personalism of Karol Wojtyla contributes to bioethical reflection in reference to woman and the feminine. The woman is a person, a unique and valuable someone, with a greater dignity, in whose freedom lies the ability to decide who she wants to be. Woman also reveals herself in action. She has a genius, a unique way of loving and being loved, of responding to the vocation to love for her full realization. Then, love constitutes her only adequate form and foundation of every ethical norm; consequently, she cannot but transmit life in all its forms. Woman displays her feminine genius from the family, from which she radiates her humanity to other areas of society. Wojtyla thus bases the contribution of woman against modern postulates such as contraception, abortion, euthanasia and other attacks on life that the culture of death brings with it. He elevates woman beyond political and social boundaries.